Involvement of AMPA Receptor GluR2 Subunits in Stimulus-Reward Learning: Evidence from Glutamate Receptor gria2 Knock-Out Mice - Mead, Andy N. (J Neurosci, 2003)
Presence of the glutamate receptor 2 (GluR2) subunit prevents calcium influx through AMPA-receptor complexes; deletion of this subunit results in enhanced hippocampal long-term potentiation. We investigated whether mice lacking the GluR2 subunit [gria2 knock-out (KO) mice] displayed impairments in learning stimulus-reward associations, and the subsequent ability of reward-paired cues to control motivated behavior. Both gria2 KO and wild-type (WT) mice learned to associate a light/tone stimulus with food delivery, as evidenced by approach toward the food magazine after the presentation of the cues (pavlovian conditioning). Subsequently, the cues also served to reinforce an operant response in both KO and WT mice (conditioned reinforcement), although response rates were greater in gria2 KOs. Responding for conditioned reinforcement was enhanced after 0.5 mg/kg amphetamine administration in WT mice, but not in KO mice. The ability of the cues to elicit approach behavior (conditioned approach) and to enhance responding for the reward (pavlovian-to-instrumental transfer; PIT) were also impaired in gria2 KO mice. This pattern of behavior resembles that seen after lesions of the central nucleus of the amygdala (CeA), an area rich in GluR2-containing AMPA receptors. Immunostaining revealed reduced GluR1 expression within both the basolateral amygdala and the CeA, suggesting that the behavioral deficits observed were unlikely to be caused by compensatory changes in GluR1. These results suggest that GluR2-containing AMPA receptors, possibly within the CeA, are critical for the formation of stimulus-reward associations necessary for PIT and conditioned approach, but are not involved in the plastic processes underlying the attribution of motivational value to the conditioned stimulus (CS).